EV71 virus-like particles produced by co-expression of capsid proteins in yeast cells elicit humoral protective response against EV71 lethal challenge. (December 2016) - Wang, Xiaowen; Xiao, Xiangqian; Zhao, Miao; Liu, Wei; Pang, Lin; Sun, Xin; Cen, Shan; Yang, Burton; Huang, Yuming; Sheng, Wang; Zeng, Yi
Abstract Background Enterovirus 71 (EV71) is the most common causative pathogens of hand, foot and mouth disease (HFMD) associated with severe neurological complications. There is a great need to develop prophylactic vaccine against EV71 infection. Results EV71 virus-like particle (VLP) was produced in yeast expression system by the co-expression of four EV71 structural proteins VP1–VP4. Immunization with the recombinant VLPs elicited potent anti-EV71 antibody responses in adult mice and anti-VLP sera were able to neutralize EV71 virus in vitro. Neonatal mice model demonstrated VLP immunization conferred protection to suckling mice against the lethal viral challenge. Conclusions Co-expression of four EV71 structural proteins VP1–VP4 in yeast expression systems is an effective method to produce EV71 VLPs. VLP-based vaccine shows great potential to prevent EV71 infection.